Almidón de caña agria (costus spicatus) como aditivo controlador de filtrado en fluidos base agua poliméricos (2020)
The oil industry has incorporated natural products since its inception for the formulation of drilling fluids as is the case of maize and potato starches, worldwide these products are part of the daily diet, making it a commercial demanding. That is why, through this research the properties of sour cane starch (Costus spicatus) were analyzed, being this plant of little national use, low cost and easy to grow; in order to determine their ability to control filtering in drilling fluids. Chemical and functional tests were carried out for the characterization of the same, obtaining a starch content of 31%, a neutral pH and an amylose/amylopectin percentage of 26.36/73.64. Drilling fluids were then formulated in concentrations of 2g, 4g, 6g and 8g and physical tested (API-13B1) compared to commercial starches. The best values were obtained for a concentration of 4g. It underwent the same physical tests with increased temperature (150oF) and was contaminated with hydrated lime. Statistically, there were no significant differences in the properties of two commercial starches under the same conditions. The function of sour cane starch as a filter controller was demonstrated.